Sensory transduction, the gateway to perception: mechanisms and pathology - Lechner, Stefan; Siemens, Jan (EMBO reports, 2011)
The 102nd biannual Boehringer Ingelheim Fonds International Titisee Conference took place in October 2010. In the welcoming atmosphere of the small lakeside resort in the Black Forest, southern Germany, scientists from around the world gathered to discuss current topics and challenges in the area of sensory biology. The research presented covered all of the classical Aristotelian senses (and beyond) and provided a glimpse at recent progress and recurring themes in the sensory systems.